A three-city comparison of drug use and drug use before sex among young men who have sex with men in the United States. Issue 1 (2nd January 2018) - Feinstein, Brian A.; Moody, Raymond L.; John, Steven A.; Parsons, Jeffrey T.; Mustanski, Brian
ABSTRACT: High rates of drug use have been documented among young men who have sex with men (YMSM). However, updated prevalence data are needed to understand current trends, especially for drug use before sex. We used baseline data from an HIV prevention trial to examine demographic differences in drug use and drug use before sex among YMSM in Atlanta, Chicago, and New York City. Marijuana was the most commonly used drug, but alkyl nitrites ("poppers"), cocaine, and Ecstasy were also commonly used. Drug use was more prevalent among older and White YMSM, and it was similar across cities, although use of poppers and polydrug use were more common in New York City. Our data generally support national prevention efforts.